2014
DOI: 10.1111/nmo.12338
|View full text |Cite
|
Sign up to set email alerts
|

Drugs acting at 5‐HT4, D2, motilin, and ghrelin receptors differ markedly in how they affect neuromuscular functions in human isolated stomach

Abstract: 5-HT4 receptor agonists show different efficacies. Motilin receptor activation has greater potential to increase gastric emptying, whereas ghrelin and D2 receptor antagonism have no direct activity. Drugs stimulating human gastric motility directly can act regardless of disease mechanisms, whereas drugs without direct activity but an ability to block nausea/vomiting may be effective only if these symptoms exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 74 publications
3
18
0
1
Order By: Relevance
“…Our results suggest that the prokinetic effect of levosulpiride is mainly caused by the increase in acetylcholine release from EMNs. This facilitatory effect has been demonstrated in the human gastric antrum, fundus and in other areas of the gastrointestinal tract such as the colon, and has been widely reported in other species such as rodents . Our results showing an increase in cholinergic EFS‐induced contractions are similar to those reported in the human antrum for the specific 5HT 4 agonist prucalopride with an E max of about 50% increase, although the potency for this specific agonist was higher .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results suggest that the prokinetic effect of levosulpiride is mainly caused by the increase in acetylcholine release from EMNs. This facilitatory effect has been demonstrated in the human gastric antrum, fundus and in other areas of the gastrointestinal tract such as the colon, and has been widely reported in other species such as rodents . Our results showing an increase in cholinergic EFS‐induced contractions are similar to those reported in the human antrum for the specific 5HT 4 agonist prucalopride with an E max of about 50% increase, although the potency for this specific agonist was higher .…”
Section: Discussionsupporting
confidence: 89%
“…This facilitatory effect has been demonstrated in the human gastric antrum, fundus and in other areas of the gastrointestinal tract such as the colon, and has been widely reported in other species such as rodents . Our results showing an increase in cholinergic EFS‐induced contractions are similar to those reported in the human antrum for the specific 5HT 4 agonist prucalopride with an E max of about 50% increase, although the potency for this specific agonist was higher . The studies are comparable because the experimental conditions were similar: we also blocked NO release and evaluated the effect on submaximal contractions, testing each dose of levosulpiride on a different sample.…”
Section: Discussionsupporting
confidence: 87%
“…It has been demonstrated to reduce esophageal acid exposure and improve gastric emptying in healthy adults, supporting its role in the management of GERD. Although previous studies found limited effects of prucalopride on esophageal motility, an in vivo study showed that its effect on esophageal motility was likely mediated by enhancing neuromuscular response as observed from muscle strips of isolated human esophageal body . The findings in this work are well supported by our previous work in that prucalopride significantly enhanced distension‐induced thresholds of secondary peristalsis triggered regardless the types of the stimuli inside the esophagus in healthy adults .…”
Section: Discussionsupporting
confidence: 87%
“…However, other works did not observe its effect on esophageal motility as studied with high‐resolution manometry . Of interest is that an in vitro study has shown its effect on esophageal motility by enhancing neuromuscular response from muscle strips of isolated human esophageal body …”
Section: Introductionmentioning
confidence: 99%
“…They concluded that ghrelin activates pelvic nerves at the sacral defecation center, innervating the enteric neurons in the distal colon (31). On the contrary, other authors have shown that ghrelin has no effect on contractility in the rat stomach, distal colon, human ascending and human sigmoid colon (32, 33). It has been suggested, from rat studies, that GHSR1a agonists affect colonic motility through actions in the CNS (34).…”
Section: Effects Of Relamorelin On Colonic Transit In Chronic Constipmentioning
confidence: 86%